Effects of surface roughness on the time-dependent wear performance of lithium disilicate glass ceramic for dental applications. (September 2021) - Meng, M.; Wang, X.S.; Li, K.Y.; Deng, Z.X.; Zhang, Z.Z.; Sun, Y.L.; Zhang, S.F.; He, L.; Guo, J.W.
Abstract: Objectives: Purpose of the present study was to evaluate the effect of surface roughness on the time-dependent wear performance of lithium disilicate (LD) glass-ceramic. Methods: Friction pairs (pin and disk specimens) were prepared by IPS e.max® Press lithium disilicate glass-ceramic. The lateral faces of friction pairs (N = 12) were grinded with silicon carbide papers, and 6 friction pairs were polished with a 0.25 μm diamond suspension after grinding. The friction pairs were tested for wear performance using a pin-on-disk tribometer with 10 N for 1.02 × 10 6 wear cycles in artificial saliva. Wear analysis of the pin and disk was performed with a 3D profilometer. The microstructure and worn surface morphology were examined with scanning electron microscopy. One-way analysis of variance and Tukey's post-hoc pairwise comparison were used to analyze the wear data. Results: The two group LD friction pairs presented strong time-dependent wear performance. The polished group (GP) exhibited a high wear rate and extensive surface wear during 0–1 × 10 5 cycles (running-in wear stage). The wear rate, height loss and surface roughness were obviously lower than those of grinded group (GG) in running-in wear stage. However, these wear parameters were similar during the steady wear stage. The worn surface topographies of the pin and disk in GP were smoother at the same cycle before the GG entering the steady wear stage. Conclusion: Running-in, which means the initial stage of wear process, is a critical period to determine the final wear loss and surface degradation, when compare the wear behavior of lithium disilicate ceramic with different initial surface states. Ceramic layer with smooth contact area leads to low wear rate and short running-in wear stage.